Expression of an Altered Ribonucleotide Reductase Activity Associated with the Replication of Murine Cytomegalovirus in Quiescent Fibroblasts - Lembo, David (American Society for Microbiology, 2000)
Ribonucleotide reductase (RNR) is an essential enzyme for the de novo synthesis of both cellular and viral DNA and catalyzes the conversion of ribonucleoside diphosphates into the corresponding deoxyribonucleoside diphosphates. The enzyme consists of two nonidentical subunits, termed R1 and R2, whose expression is very low in resting cells and maximal in S-phase cells. Here we show that murine cytomegalovirus (MCMV) replication depends on ribonucleotide reduction since it is prevented by the RNR inhibitor hydroxyurea. MCMV infection of quiescent fibroblasts markedly induces both mRNA and protein corresponding to the cellular R2 subunit, whereas expression of the cellular R1 subunit does not appear to be up-regulated. The increase in R2 gene expression is due to an increase in gene transcription, since the activity of a reporter gene driven by the mouse R2 promoter is induced following virus infection. Cotransfection experiments revealed that expression of the viral immediate-early 1 protein was sufficient to mediate the increase in R2 promoter activity. It was found that the viral gene M45, encoding a putative homologue of the R1 subunit, is expressed 24 and 48 h after infection. Meanwhile, we observed an expansion of the deoxyribonucleoside triphosphate pool between 24 and 48 h after infection; however, neither CDP reduction nor viral replication was inhibited by treatment with 10 mM thymidine. These findings indicate the induction of an RNR activity with an altered allosteric regulation compared to the mouse RNR following MCMV infection and suggest that the virus R1 homologue may complex with the induced cellular R2 protein to reconstitute a new RNR activity.